The music of Joji Yuasa - Galliano, Luciana, 1953- (Cambridge Scholars Publishing, 2012)
Over the last fifty years, the music of Joji Yuasa has attained the zenith of international musical standards: a study of this great Japanese composer is long overdue. Persuasive and captivating, less 'easy' than that of his lifetime friend Toru Takemitsu, Yuasa's music has also been a model for many young composers, both from Japan and further afield, thanks to the long period he spent teaching composition at the University of California, San Diego (1981-1994). This book serves to illumina ...